FUNGSI KIASAN PATAH HATI BAHASA BALI DALAM GEGURITAN “SAMPIK” (The Function of Balinese Figure of Speech on Broken Heart in Geguritan Sampik) - I Ketut Wardana (Kantor Bahasa Provinsi Sulawesi Tenggara, 2022)
This study aimed to examine the form, function, and meaning of Balinese expressions from the perspective of systemic functional linguistic theory (SFL). This study used a phenomenological-based approach. The data consisted of 51 stanzas and each stanza contained 7 to 9 lines collected through document analysis and they were classified into language meta function elements. The data were analyzed through the classification of the content of the text, the characteristics of the text, and the application of the SFL model. The findings of this study indicate that Gaguritan Sampik has 4 types of figures of speech, namely similes, metaphor, hyperbole, and personification with comparative meaning that bridges cognitive meaning to imaginative meaning. The findings of the LSF analysis show that all of the poems in Gaguritan Sampik have ideational, interpersonal, and textual metafunction elements, but this model cannot access chronological stages and holistic meanings due to position shifting, phrase deletion, or phrase duplication in the literary writing system. However, the LSF model proves that a coherent and coherent figure of speech mechanism can evoke the reader's imagination so that it absorbs philosophical values in the text. Penelitian ini bertujuan untuk mengkaji bentuk, fungsi, dan makna kiasan ungkapan majas patah hati bahasa Bali dalam geguritan “Sampik” dari perspektif teori linguistik sistemik fungsional (LSF). Penelitian ini menggunakan pendekatan kualitatif berbasis fenomenologi. Data terdiri atas 51 stanza dan tiap stanza terdiri atas 7 sampai 9 baris dikumpulkan melalui analisis dokumen dan diklasifikasikan ke dalam unsur metafungsi bahasa. Data dianalisis melalui tahapan klasifikasi isi teks, karakteristik teks, dan penerapan model LSF. Temuan penelitian ini menunjukkan bahwa geguritan “Sampik” memiliki empat jenis majas, yaitu perbandingan, metafora, hiperbola, dan personifikasi dengan makna komparatif yang menjembatani makna kognitif menuju makna imajinatif. Temuan analisis LSF menunjukan semua syair pada geguritan “Sampik” memiliki unsur-unsur metafungsi ideasional, interpersonal, dan tekstual, tetapi model ini tidak dapat mengakses tahapan kronologis dan makna secara holistik akibat adanya pemindahan posisi, pelesapan prasa, atau duplikasi prasa pada sistem penulisan sastra. Walaupun demikian, model LSF membuktikan bahwa mekanisme majas yang runut dan padu dapat membangkitkan imaji pembaca sehingga meresapi nilai filosofis dalam teks.